2017
DOI: 10.1021/acs.orglett.7b00727
|View full text |Cite
|
Sign up to set email alerts
|

Design and Applications of N-tert-Butyl Sulfinyl Squaramide Catalysts

Abstract: A new chiral HBD system, N-tert-butyl sulfinyl squaramide, was designed and synthesized. The core N-tert-butyl sulfinyl squaramide with an 1-aminoindan-2-ol skeleton was found to be an efficient catalyst in the enantioselective Friedel-Crafts alkylation of indoles and acyl phosphonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Also, it has been found that the C–H···O hydrogen-bonding interactions could serve as a key factor in controlling stereoselectivity . Recently, our group developed a novel N - tert -butyl sulfinyl squaramide, in which the N - tert -butyl sulfinyl group enhances the lipophicity and acidity of squaramide . The novel N - tert -butyl sulfinyl squaramide successfully catalyzed the enantioselective Friedel–Crafts alkylations of indoles and acyl phosphonate.…”
Section: Introductionmentioning
confidence: 96%
“…Also, it has been found that the C–H···O hydrogen-bonding interactions could serve as a key factor in controlling stereoselectivity . Recently, our group developed a novel N - tert -butyl sulfinyl squaramide, in which the N - tert -butyl sulfinyl group enhances the lipophicity and acidity of squaramide . The novel N - tert -butyl sulfinyl squaramide successfully catalyzed the enantioselective Friedel–Crafts alkylations of indoles and acyl phosphonate.…”
Section: Introductionmentioning
confidence: 96%
“…3-Halooxindoles with both nucleophilicity and eletrophilicity at the C-3 position have been entailed in many elegant annulation reactions to date, giving various highly substituted spirocyclic oxindoles . On the other hand, α,β-unsaturated acyl phosphonates were proved to be robust electron-deficient olefins and often serve as activated ester surrogates in organic synthesis . Recently, we documented DMAP-catalyzed 1,3-dipolar cycloaddition of azomethine ylides with α,β-unsaturated acyl phosphonates, furnishing a class of spiropyrrolidinyl-2,3′-oxindoles with high efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed the hydrogen‐bonding donor compound, N ‐ tert ‐butyl sulfinyl squaramide, in which the N‐tert ‐butyl sulfinyl group serves as a hydrogen‐bond acceptor and enhances the lipophilicity as well as the acidity of the squaramide. In our previous study, we found that N‐tert ‐butyl sulfinyl squaramide has better hydrogen‐bonding donor abilities than traditional squaramide.…”
Section: Introductionmentioning
confidence: 99%